The role of innovation and organisational agility to drive strategic capabilities: a case of Eswatini revenue services (ERS) - Vermaak, Andre (University of Pretoria, 2026)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2025.